Study on the gear-rack meshing dynamic performance based on a multi-body dynamic model of rack rail vehicle - Shen, Longjiang; Zhou, Zuobin; Wu, Xingwen; He, Shizhong; Yang, Ningrui; Luo, Yang (Advances in mechanical engineering, 2024)
Rack rail vehicles show strong capability of mountain climbing and have become a popular transportation mode for mountain areas in recent years. Therefore, this paper investigated on the dynamic performance of rack rail vehicle through simulation of a multibody dynamic model. Firstly, a multibody dynamic model of rack rail vehicle considering both the wheel/rail interaction and the gear-rack meshing was developed in the SIMPACK software platform. A rack rail with a large slope of 250‰ was taken into consideration in the proposed study. Subsequently, the gear-rack meshing dynamics in terms of the meshing stiffness and the meshing force in both circumferential- and radial- directions were investigated. Moreover, two types of driving modes were compared to illustrate the effects of driving mode on the wheel/rail interaction and the gear-rack meshing. The results show that due to the gear-rack meshing the meshing stiffness and the meshing force are subject to the periodical variations and the gear-rack meshing can significantly affect the wheel/rail interaction, especially in the presence of track irregularities. The driving mode that the gear wheel is installed on the wheelset axle through a hollow shaft is considered as a more practical design for the rack vehicle.